Hepatozoon in Eurasian red squirrels Sciurus vulgaris, its taxonomic identity, and phylogenetic placement - Modrý, David; Hofmannová, Lada; Papežík, Petr; Majerová, Karolina; Votýpka, Jan; Hönig, Václav; Růžek, Daniel; Hrazdilová, Kristýna (Parasitology research, 2021)
Adeleorid apicomplexan parasites of the genus Hepatozoon Miller, 1908 are broadly distributed among the rodents. Broader molecular data on Hepatozoon from Palaearctic squirrels are necessary for evaluation of diversity and origin of Hepatozoon in Eurasian red squirrel Sciurus vulgaris populations, considering ongoing invasion by Gray squirrel S. carolinensis. Our report brings a set of molecular data from a population of S. vulgaris in the Czech Republic, non-invaded by any invasive squirrel species. Cadavers of 41 Eurasian red squirrels were examined using nested PCR targeting 18S rRNA gene; 30 animals tested positive for the presence of Hepatozoon spp. DNA in at least one tissue. Phylogenetic analysis of obtained sequence types revealed relatedness to sequences of Hepatozoon sp. from S. vulgaris from Spain and the Netherlands, forming a sister clade to Hepatozoon isolates from other European rodents. The fact that all available 18S rRNA gene sequences form a monophyletic clade is interpreted as a presence of a single Hepatozoon species in S. vulgaris in continental Europe, most probably Hepatozoon sciuri. The presented molecular data on the Hepatozoon from European squirrels provides a basis for future studies on possible exchange of Hepatozoon species between Eurasian red and gray squirrels.
Keywords: Animals; Česká republika; Phylogeny; Eucoccidiida; RNA, Ribosomal, 18S; Europe; zvířata; Squirrel; fylogeneze; 18S rRNA gene; Czech Republic; Sciuridae; Hemoparasites; RNA ribozomální 18S; Hepatozoon; Sciurus